How does education promote green digital finance? Evidence from China - Chien-Chiang Lee; Fuhao Wang; Chi-Chuan Lee (Financial Innovation)
Abstract This study constructs a new composite green digital finance index and describes its development in China over the past decade. Based on province-level panel data covering the period 2011–2020, we examine how education contributes to the development of green digital finance. Through detailed theoretical analysis and rigorous empirical testing, the following results are obtained. First, education directly promotes green digital finance by adjusting people’s consciousness and enhancing their abilities. Second, high-quality educational inputs, a high level of economic development, and a high degree of opening-up are among the important preconditions for education to further promote green digital finance in China. Third, education indirectly promotes green digital finance by driving industrial upgrades, increasing income levels, promoting technological innovation, and cultivating finance-related talent. This study offers policy recommendations to help improve education levels and suggests a valuable direction for further research on green digital finance.